Use of Geospatial Mapping to Determine Suitable Locations for Patient Service Centers for Phlebotomy Services. Issue 5 (1st November 2015) - Baskin, Leland; Abdullah, Amid; Guo, Maggie; Naugler, Christopher
Abstract: Objectives: Approaches to determining optimal locations for patient service centers (phlebotomy clinics) have not been addressed in the published literature. Using the city of Calgary, Alberta, Canada, as a test case, our objective is to present a novel method for determining underserviced geographic areas within a city to guide the choice of potential new patient service center locations. Methods: Data on travel distances for 198, 883 phlebotomy visits as well as population data from the 2011 Canada Census were used for this study. Using geospatial mapping techniques, we produced maps of the city showing actual relative travel distances for patients as well as the geographic distribution of population density of patients undergoing phlebotomies. Results: There was a striking pattern of increased travel distances in certain parts of the city. These also corresponded to geographic areas with greater density of patients seeking phlebotomies. Conclusions: This analysis provided clear, objective evidence of communities that are currently relatively underserved by patient service centers. This approach could be used by other laboratories to plan the location of new patient service centers.